Spermatogenesis, sperm storage and reproductive timing in bats. (16th November 2012) - Pfeiffer, B.; Mayer, F.
Abstract: Reproduction in bats from the temperate zones differs from the general mammalian pattern with regard to long‐term sperm storage. In contrast to other mammals, female bats from the temperate zones store viable spermatozoa from autumn copulations through hibernation into spring when fertilization occurs. Males, however, are also capable of storing spermatozoa viably in their cauda epididymides after they have undergone spermatogenesis in the summer months. This could free them from precisely coupling their spermatogenic timing to the female cycle. Furthermore, it enables them to inseminate females throughout winter during periodic arousals and into spring. In this comparative study of four sympatric species at one site in Central Europe, we tested for interspecific differences in the onset and length of the mating period. Species‐specific mating periods can be best explained by the availability of receptive females since males match the timing of spermatogenesis closely to the female reproductive cycle. The close sequence of male reproductive readiness and female availability indicates a fertilization advantage of early copulations in hibernating bats, as opposed to last sperm precedence in most mammals. Thus, the observed marked differences in the timing of reproduction between these sympatric species are in contrast to the hypothesis that reproductive timing results solely from climate and food availability.